Kesadaran tentang Kesehatan Mental untuk Siswa dan Orang Tua Siswa di SMP X - Anindya Dewi Paramita; Andi Tenri Faradiba (Fakultas Psikologi Universitas Pancasila, 2024)
Many factors contribute to adolescents’ mental health, from changes within themselves to the outside world, which make adolescents vulnerable to mental health problems. In recent years, mental health issues have also begun to become a concern for educational institutions, including X Junior High School. In the last two years, several students have mental problems that interfere with their daily and academic functioning. Therefore, it is necessary to carry out some kind of follow-up action to prevent the development of mental health problems among students. Psychoeducational activities with the aim of increasing knowledge and awareness regarding maintaining mental health are carried out and provided to students and parents of grades VII and VIII face-to-face (offline) in the school. The results of this psychoeducation activity are that both students and parents have begun to demonstrate mental health literacy, although it is not yet comprehensive. Students know practical ways to deal with unpleasant situations, so it would be good if there was more specific training regarding self-management skills. At the end of the session the parents came to the conclusion that what is needed is not only understanding children who are in their teenage years but also considering what forms of interaction and assistance are suitable and acceptable for children. In the future, similar activities are also needed for schools to create a supportive environment for adolescents.